Hellenistic poets on the origin of the Nile: A poetic commentary on a geographical problem - A. M. Malomud (Шаги)
The paper deals with passages from Theocritus (7.113–114), Callimachus (H. 4.206–208), Nicander (Ther. 174–176), and Oppian (Hal. 1.620), united by the joint mention of the Nile and the Ethiopians. The appearance of these two details within the same verse/sentence can be interpreted as an allusion to one of the debatable questions of ancient geography — the location of the sources of the Nile. It is likely that here we are dealing with a special type of allusion: each of the poets in question refers not to a specific place or text, but to a scientific problem, awareness of which he wants to demonstrate. The author concludes that such geographical allusions can be regarded as an implicit commentary and are similar to the poetic technique of so-called interpretatio Homerica (the use of a Homeric hapax, in which the context itself contains the author’s opinion on the correct interpretation of a particular rare word). In connection with the passages from Theocritus and Oppian, the problem of “double” Ethiopians — western and eastern — is also relevant. The article pays attention to the origins of this (Hom. Od. 1.23–24) and also considers interpretations of this Homeric place in Herodotus’ Histories, Aeschylus’ Prometheus Bound and Pliny’s Natural History.